2016
DOI: 10.1177/0037549716630605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dual-frequency combination on the quality improvement of ultrasound tomography

Abstract: The most useful feature of ultrasound tomography founded on the inverse scattering theory is that it can detect small structures below the wavelength of the pressure wave. A popular method introduced in ultrasound tomography is the Distorted Born Iterative Method (DBIM). Recently, the dual-frequency combination technique has been utilized to improve the reconstruction quality and increase the convergence rate of the DBIM. This method uses two frequencies, f 1 (low) and f 2 (high), to estimate the sound contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Fig. 5 also confirmed that using multi-frequency DBIM image reconstruction offers better performance than conventional DBIM and our previous study (Tran et al, 2016). The technique of using multi-frequency is realistic because the ultrasound probes now a large frequency bandwidth.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Fig. 5 also confirmed that using multi-frequency DBIM image reconstruction offers better performance than conventional DBIM and our previous study (Tran et al, 2016). The technique of using multi-frequency is realistic because the ultrasound probes now a large frequency bandwidth.…”
Section: Discussionsupporting
confidence: 85%
“…The reason behind this is the relatively small difference between the true contrast and initial contrast (Born approximation satisfied). In (Jonathan & Oelze, 2013), (Tijhuis et al, 2001), (Lavarello & Oelze, 2010), (Tran et al, 2016), the authors suggested using more than two frequencies to get the resolution of a tomographic ultrasound image closer to the level of tissue image reconstruction. Not only for ultrasound tomography, the multiple -frequency technique is also applied for ultrasound images in (Ma et al, 2015;Sayed, 2018;Varray et al, 2012;Yoshizumi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the recovered images by this scheme is better than that of the DBIM, and the computation time is also significantly reduced. The multi-frequency (MF) technique has been studied and applied to the DBIM in [25][26][27][28][29][30][31][32][33][34][35][36][37]. This approach is applied as follows: in the first step, the lower frequency acquired data are used to ensure fast convergence, and in the second step, the higher frequency acquired data are used to ensure the high resolution of the reconstructed image.…”
Section: Methodsmentioning
confidence: 99%